A feminist critique on the use of the Internet in nursing research. - Im E; Chee W (Advances in Nursing Science, 2001)
With the increasing use of the Internet, the importance of incorporating this new technology in nursing research increases. Yet nursing has been slow in adopting this new technology as a research method, and the use of the Internet in nursing research rarely has been discussed and critiqued. In this article, use of the Internet in nursing research is analyzed and critiqued from a feminist perspective. The analysis indicates that use of the Internet in research frequently brings about selection biases because of a limited pool of potential participants, it usually does not provide contextual data on research encounters, it might not uncover women's subjective experiences under marginalized situations, and it tends to raise power issues related to the relationships between researchers and participants. Despite the limitations, use of the Internet in research provides better communication channels for research participants, more flexibility in time and place of data collection, and less expense for data collection. Based on the critique, feminist challenges for future use of the Internet in nursing research are proposed. Copyright © 2001 by Aspen Publishers, Inc.